The Role of Interpersonal Communication in Conflict Management and Organizational Culture Formation in the Badung Regency General Election Commission Agency - I Nyoman Windu Surya Sidantha; Ni Nyoman Cipta Dewi; I Putu Hugo Kusuma; Ni Made Cahya Dwipayanti; Ni Made Sonia Wulandari (COMMUSTY Journal of Communication Studies and Society, 2025)
This study aims to analyze in depth the strategic role of interpersonal communication in the conflict management process and its contribution to the formation of organizational culture in the General Election Commission (KPU) of Badung Regency. In the context of high-complexity public organizations such as the KPU, interpersonal communication not only functions as a channel of information but also as the main instrument in creating mutual understanding, strengthening social cohesion, and encouraging the creation of a harmonious and productive work atmosphere. This study uses a qualitative descriptive approach with a literature study method, where data is collected and analyzed narratively through relevant scientific literature. The results show These, Interpersonal communication plays a very vital and strategic rolein supporting the effectiveness of conflict management while contributing significantly to the process of forming organizational culture within the Badung Regency General Election Commission. Communication between individuals in organizations, both formal and informal, has proven to function not only as a means of information exchange, but also as a relational instrument that creates mutual understanding, builds trust, and strengthens social cohesion between employees. More specifically, this study found that open, empathetic, and participatory interpersonal communication patterns are able to be an effective medium in preventing, mitigating, and resolving internal conflicts that arise as a consequence of organizational work dynamics.